Programme Accreditation in Tertiary Education - Niyi Jacob Ogunode; Kingsley Edinoh; RAUF, Olaiya Sarafadeen (Journal of Higher Education and Academic Advancement, 2024)
Programme accreditation is crucial to tertiary institutions because of its ability to ensure quality assurance in the system. Programme accreditation is a mechanism designed in the tertiary institutions to ensure that academic programmes offered are of standard and meet various policies and quality of national and international standard. This paper discussed the barriers to effective programme accreditation in tertiary institutions in Nigeria. Employing secondary data that were obtained from online publications and print resources. The paper concluded that inadequate funding, shortage of academic staff, inadequate infrastructural facilities, brain-drain and strike actions are the barriers to effective programme accreditation in tertiary institutions in Nigeria. Based on these barriers identified, the paper recommended the following; increment in budgetary allocation to the tertiary institutions, employment of more adequate staff, provision of adequate infrastructural facilities, increment in salaries and welfare allowances of academic staff and implementation of agreement entered into with various unions in the tertiary institutions to prevent strike actions.